Women working at university restaurants: life and work conditions and gender-based violence - Kelly Cristina Maxima Pereira Venancio; Rosa Maria Godoy Serpa da Fonseca (SciELO, 2013)
This is an exploratory and descriptive study with a quantitative approach that aimed to understand the social production and reproduction processes of women working at university restaurants and the occurrence and the magnitude of gender-based violence committed against them by their intimate partners. The data were collected through semi-structured interviews. The analysis categories used were social production and reproduction, gender and gender-based violence. The interviewees held a subordinate social position during the productive and reproductive periods of their lives. Approximately 70% reported having experienced gender-based violence from an intimate partner (66% psychological violence, 36.3% physical violence and 28.6% sexual violence). Most of the health problems resulting from violence were related to mental health. The results indicate that the situation requires immediate interventions, mostly guided by the instrumentalization of these women and the support by the state and the university as appropriate to address violence.